Emerging global trade governance mega free trade agreements and implications for ASEAN - Chen, Lurong; Urata, Shūjirō 1950-; Nakagawa, Junji 1955-; Ambashi, Masahito (Routledge, 2019)
"Mega free trade agreements (FTAs) are being formed to fill the gap created by new developments in global governance and are reshaping the world economic order. The Trans-Pacific Partnership (TPP) agreement is one of such 21st century FTAs. This book highlights three trade-related issues covered by the TPP that greatly concern emerging countries - investment, intellectual property rights (IPR), and state-owned enterprises (SOEs). It contains rigorous economic, legal, and political analyses on the final text of the agreement, combined with country-specific policy discussions focusing on Indonesia, the Philippines, Thailand, and Viet Nam, giving readers insights on the establishment of global rules and regulations for 21st century trade. The book also outlines the requirements for emerging Asian countries to better formulate trade policies in the new era of international trade and promote regional integration in ASEAN and East Asia"--
Description based on print version record
Keywords: ASEAN.; Trans-Pacific Strategic Economic Partnership Agreement / (2005 June 3); Free trade / Pacific Area